Zinc Limitation Induces a Hyper-Adherent Goliath Phenotype in Candida albicans - Malavia, Dhara; Lehtovirta-Morley, Laura E.; Alamir, Omran; Weiß, Elisabeth; Gow, Neil A. R.; Hube, Bernhard; Wilson, Duncan (Frontiers in Microbiology, 2017)
Pathogenic microorganisms often face acute micronutrient limitation during infection due to the action of host-mediated nutritional immunity. The human fungal pathogen Candida albicans is polymorphic and its morphological plasticity is one of its most widely recognised pathogenicity attributes. Here we investigated the effect of zinc, iron, manganese and copper limitation on C. albicans morphology. Restriction of zinc specifically resulted in the formation of enlarged, spherical yeasts, a novel morphotypephenotype which we term Goliath cells. This morphological cellular response to zinc restriction was conserved in C. albicans, C. dubliniensis and C. tropicalis, but not in C. parapsilosis, C. lusitaniae or Debaryomyces hansenii, suggesting that it may have emerged in the last common ancestor of these related pathogenic species. Cell wall analysis revealed proportionally more chitin exposure on the Goliath cell surface. Importantly, these cells were hyper-adherent, suggesting a possible role in pathogenicity. Interestingly, the zincophore-encoding gene PRA1 was expressed in Goliath-inducing media and lack of Pra1 inhibited both cellular enlargement and adhesion. Goliath cells represent a further layer of Candida morphological complexityphenotypic plasticity.